Eco-design based on ontology: State of the art and directions - Mohammed, Moseed Abdullah Yahia; Awanis, Romli; Rozlina, Mohamed (AIP Publishing, 2023)
The present study addresses the sustainability assessment which is interest to many researchers and provides opportunities to measure and evaluate sustainability achievement; sustainable environment has become essential to product innovations that protect public health and environment over their whole life cycle. The lack of using knowledge is the critical challenges in assessing of the social, economic, and environment impacts at all phases of the product life cycle start from the selection of raw material, manufacturing, use, and waste disposal. The aim is to support decision-making by manufacturers to integrate and devise alternatives to conserve the environment, especially in the early stages of product design. What is ontology? What difficulties have been overcome until now by ontology? What is the effective role of ontology in sustainability? This paper seeks to address these questions; the researchers pointed to the importance of using the ontology to address the impacts of products through the outputs of the product life cycle assessment tool. © 2023 American Institute of Physics Inc.